The Influence Of English Mastery And Competencies On Students' Readiness To Enter The World Of Work - Syamsudin, Syamsudin (Jurnal Scientia, 2024)
This research aims to analyze the influence of English language mastery and competency on students' readiness to enter the world of work. Mastery of English is considered important in the era of globalization, while competencies that include technical, interpersonal and managerial skills play a key role in determining the work readiness of college graduates. The research method used is a quantitative approach with a survey design. Data were collected from final year students at the University, using a structured questionnaire. The data analysis technique used is path analysis to examine the influence of English language mastery and competency on students' readiness to enter the world of work. The research results show that both English language mastery and competency have a significant effect on students' work readiness. This research provides an impression for higher education institutions to strengthen students' English language and competency development programs in order to increase their readiness to face the challenges of the world of work.